Paradoxes of Pardha and Agency among Muslim women in Kerala - Abdelhalim, Julten (Lidé města, 2013)
Following the oil boom of the 1970s in the Arabian Gulf, the region witnessed massive labour migration waves from the Southwestern Indian state of Kerala. The impact of the migration on the Arabian Gulf countries led to unprecedented advancements in the human development index of Kerala, especially among Muslims who were most affected by the tremendous social change. In this paper, I focus on only one sign of this socio-cultural change that was reflected in the adoption of the female Arab black attire, termed pardha in Kerala. What I will be arguing through the coming pages is the paradoxical formula where pardha was enforced as a marker of identity, but had nevertheless created emancipatory tools out of the confining frameworks of traditional patriarchy as characteristic of much of Keralite society. This paper seeks to convey the different debates surrounding this phenomenon and what women themselves have to say about it. This paper focuses on fieldwork undertaken in two districts of northern Kerala or what is known as Malabar, namely Malappuram and Kozhikode.